Des aiguisoirs/polissoirs aux enclumes en os : l’historiographie des os piquetés - Isabelle Rodet-Belarbi; Montserrat Esteban Nadal; Vianney Forest; Marta Moreno-Garcia; Carlos Pimenta (Archéologie Médiévale)
Since the end of the 19th century, a lot of animal bones with particular marks have been discovered in Midi-Pyrénées (France). The most common bones come from Equus sp. and Bos t. and are often metapods. The faces of the bone have been wittled down, smoothed, and present rows of triangular-shaped dents. Many interpretations have been given for the French tools. The last of these, a sharpener/polisher hypothesis, is contradicted by the publication of ethnographical bone anvils from the Iberian peninsula.